The Impact of Interest Rate Changes on Economic Activities in Indonesia - Franata Milala; Sanusi Gazali Pane; Agita Crysti; Enjel Kristian Zai (Universitas Dehasen Bengkulu, 2026)
Changes in interest rates are one way the government manages state finances which greatly influences economic conditions, including in Indonesia. This research wants to see how changes in interest rates affect various aspects of the economy, such as economic growth, investment, public spending, and the inflation rate. To analyze this, researchers used quantitative methods with data from various official sources such as Bank Indonesia, the Central Statistics Agency, and other institutions over a certain period of time. The techniques used include descriptive analysis and regression to see the relationship between interest rates and macroeconomic variables. Research results show that when interest rates rise, it usually reduces the amount of investment and public spending, thereby slowing the rate of economic growth. On the other hand, if interest rates fall, it can encourage economic growth because it increases investment and people's purchasing power, but it can also increase inflation. Therefore, in determining interest rates, the government must be careful and balanced so that the economy remains stable. It is hoped that this research can help in realizing a better and more sustainable monetary policy in Indonesia.